Pan‐European phylogeography of the European roe deer (Capreolus capreolus). Issue 5 (19th May 2022) - Plis, Kamila; Niedziałkowska, Magdalena; Borowik, Tomasz; Lang, Johannes; Heddergott, Mike; Tiainen, Juha; Bunevich, Aleksey; Šprem, Nikica; Paule, Ladislav; Danilkin, Aleksey; Kholodova, Marina; Zvychaynaya, Elena; et al.
Abstract: To provide the most comprehensive picture of species phylogeny and phylogeography of European roe deer ( Capreolus capreolus ), we analyzed mtDNA control region (610 bp) of 1469 samples of roe deer from Central and Eastern Europe and included into the analyses additional 1541 mtDNA sequences from GenBank from other regions of the continent. We detected two mtDNA lineages of the species: European and Siberian (an introgression of C .  pygargus mtDNA into C .  capreolus ). The Siberian lineage was most frequent in the eastern part of the continent and declined toward Central Europe. The European lineage contained three clades (Central, Eastern, and Western) composed of several haplogroups, many of which were separated in space. The Western clade appeared to have a discontinuous range from Portugal to Russia. Most of the haplogroups in the Central and the Eastern clades were under expansion during the Weichselian glacial period before the Last Glacial Maximum (LGM), while the expansion time of the Western clade overlapped with the Eemian interglacial. The high genetic diversity of extant roe deer is the result of their survival during the LGM probably in a large, contiguous range spanning from the Iberian Peninsula to the Caucasus Mts and in two northern refugia. Abstract : Among European ungulates, the roe deer ( Capreolus capreolus ) is the most widely distributed species and we decided to investigate how the past features impacted the current genetic patterns of this species. With the approach of the large‐scale sampling, we decided to fill gaps in knowledge and prepare the most comprehensive study about roe deer genetic in Europe. We also took an attempt to define possible areas, important for the species survival during Last Glacial Maximum.